2013
DOI: 10.2215/cjn.12311212
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Burden and Perioperative Complications for Living Kidney Donors in the United States

Abstract: Background and objectives Since 1998, 35% of kidney transplants in the United States have been derived from living donors. Research suggests minimal long-term health consequences after donation, but comprehensive studies are limited. The primary objective was to evaluate trends in comorbidity burden and complications among living donors.Design, setting, participants, & measurements The National Inpatient Sample (NIS) was used to identify donors from 1998 to 2010 (n=69,117). Comorbid conditions, complications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 34 publications
4
48
2
Order By: Relevance
“…Despite relatively reassuring data regarding the long-term health of donors, follow-up care is essential to monitor progress, identify morbidity, and facilitate any potential need for interventions (1)(2)(3)(4)(5)(6). In addition, there has been an increased rate of living donors with complex medical conditions, rendering vigilant monitoring for any potential health consequences of donation increasingly important (7)(8)(9)(10). Prior reports have indicated a lack of complete reporting of kidney donor follow-up on standard United Network for Organ Sharing (UNOS) forms (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Despite relatively reassuring data regarding the long-term health of donors, follow-up care is essential to monitor progress, identify morbidity, and facilitate any potential need for interventions (1)(2)(3)(4)(5)(6). In addition, there has been an increased rate of living donors with complex medical conditions, rendering vigilant monitoring for any potential health consequences of donation increasingly important (7)(8)(9)(10). Prior reports have indicated a lack of complete reporting of kidney donor follow-up on standard United Network for Organ Sharing (UNOS) forms (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…On the background of uncertainty regarding the true distribution of perioperative complications after donor nephrectomy, a new article by Schold et al illustrates an innovative approach (6). Using data from the Nationwide Inpatient Sample (NIS), an all-payer inpatient care database comprising a stratified sample of 20% of nonfederal United States hospitals from participating states, the investigators identified living kidney donors in 1998-2010 on the basis of International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis and procedure codes.…”
mentioning
confidence: 99%
“…With the evolution in surgical techniques for donor nephrectomy [24], perioperative outcomes are excellent [6, 20, 2529] and continue to improve, despite increasing donor comorbidity [29]. Survival from nephrectomy is outstanding, with a perioperative death rate of 0.03 % [6, 25].…”
Section: Overall Outcomes Of Living Donorsmentioning
confidence: 99%
“…In multivariate analysis, donors with SBP ≥ 140 had significantly higher rates of death than those with measurements < 120 mmHg [25]. More recently, donor hypertension was found to be an independent predictor of longer hospital length of stay and surgical complications [29]. …”
Section: Medical Complexities At Donation and Associated Outcomesmentioning
confidence: 99%